Investigation of Cannabinoid Acid/Cyclodextrin Inclusion Complex for Improving Physicochemical and Biological Performance - Park, Chulhun; Zuo, Jieyu; Gil, Myung Chul; Löbenberg, Raimar; Lee, Beom Jin (Pharmaceutics, 2023)
This study aimed to investigate the enhancement of cannabinoid acid solubility and stability through the formation of a cannabinoid acid/cyclodextrin (CD) inclusion complex. Two cannabinoid acids, tetrahydro-cannabinolic acid (THCA) and cannabidiolic acid (CBDA), were selected as a model drug along with five types of CD: α-cyclodextrin (α-CD), β-cyclodextrin (β-CD), γ-cyclodextrin (γ-CD), hydroxypropyl-β-cyclodextrin (HP-β-CD), and methylated-β-cyclodextrin (M-β-CD). Phase solubility studies were conducted using various types of CD to determine the complex stoichiometry. The preparation methods of the CD inclusion complex were optimized by adjusting the loading pH solution and the drying processes (spray-drying, freeze-drying, spray-freeze-drying). The drying process of the cannabinoid acid/M-β-CD inclusion complex was further optimized through the spray-freeze-drying method. These CD complexes were characterized using solubility determination, differential scanning calorimetry (DSC), field-emission scanning electron microscopy (FE-SEM), X-ray diffraction (XRD), and 1H NMR spectroscopy. DSC, XRD, and FE-SEM studies confirmed the non-crystalline state of the cannabinoid acid/CD inclusion complex. The permeation of THCA or CBDA from the M-β-CD spray-freeze-dried inclusion complex was highly improved compared to those of cannabis ethanolic extracts under simulated physiological conditions. The stability of the cannabinoid acid/M-β-CD inclusion complex was maintained for 7 days in a simulated physiological condition. Furthermore, the minimum inhibitory concentration of cannabinoid acid/M-β-CD inclusion complex had superior anti-cancer activity in MCF-7 breast cancer cell lines compared to cannabinoid acid alone. The improved physicochemical and biological performances indicated that these CD inclusion complexes could provide a promising option for loading lipophilic cannabinoids in cannabis-derived drug products.
Keywords: anti-cancer activity; cannabinoid acid; inclusion complex; methylated β-cyclodextrin; permeability; solubility; spray-freeze-drying; stability